2014
DOI: 10.1002/adma.201401537
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Nanofibrous Polymeric Substrates for Generating Elastic and Flexible Electronics

Abstract: Biodegradable nanofibrous polymeric substrates are used to fabricate suturable, elastic, and flexible electronics and sensors. The fibrous microstructure of the substrate makes it permeable to gas and liquid and facilitates the patterning process. As a proof‐of‐principle, temperature and strain sensors are fabricated on this elastic substrate and tested in vitro. The proposed system can be implemented in the field of bioresorbable electronics and the emerging area of smart wound dressings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
117
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 40 publications
1
117
0
Order By: Relevance
“…Typical biodegradable polymeric substrate materials are -polydimethylsiloxane, low density poly-ethylene, poly-vinyl alcohol, polyimide, polyethylene glycol and cellulose. [2][3][4][5][6][7] Except for cellulose, all other polymers need to be synthesized while cellulose is naturally occurring and is sustainable. It is produced by both plants and bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Typical biodegradable polymeric substrate materials are -polydimethylsiloxane, low density poly-ethylene, poly-vinyl alcohol, polyimide, polyethylene glycol and cellulose. [2][3][4][5][6][7] Except for cellulose, all other polymers need to be synthesized while cellulose is naturally occurring and is sustainable. It is produced by both plants and bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that CNF substrates derived from wood 2,3 have good mechanical properties, low thermal expansion, good flexibility, and good biodegradability [4][5][6][7] and thus have the potential to serve as substrates for portable green electronics. Researchers have previously demonstrated the use of cellulose nanofibril composites as substrates for a variety of energy and electronic devices such as solar cells, [8][9][10] energy storage devices, 11 sensors, 12 organic TFTs, 13 lighting devices, 14 and displays.…”
mentioning
confidence: 99%
“…Recent technological advances in the miniaturization of sensors and the fabrication of smart materials have progressively changed the landscape of health care by providing the ability to develop devices that can continuously monitor a patient's health status [1][2][3][4][5] . Examples of such devices are electrocardiogram electrodes, temperature sensors, pH sensors, and flexible batteries that have been used for real-time health monitoring [6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Several paper-based platforms have been developed recently, such as lateral flow immunoassays for the detection of analytes 18,19 , detection of DNA or proteins 20 , and electrochemical biosensing 21,22 . Recently, nanofibrous polymeric substrates have been developed to fabricate elastic and flexible electronics that can be sutured 3 . The fibrous microstructure of the substrate enables gas and liquid permeation and promotes the ability to pattern metallic electrodes on them.…”
Section: Introductionmentioning
confidence: 99%